Handbook of Media and Communication Economics: A European Perspective - Krone, Jan; Pellegrini, Tassilo (Springer Fachmedien Wiesbaden, 2022)
This handbook maps the media economy in its entirety against the background of the advancing digitalization of communication, media production, media distribution and the adaptation of regulatory framework conditions from different disciplinary approaches. It provides an integrated view on digitally induced economic transformations of the European media sector, and gives an explicitly European perspective on media economics – challenging the dominant US-American view. Topics covered include, but are not limited to: Theoretical approaches to media economics; media technologies and data management in media economics; building blocks of the media industry; media types and core distribution markets; system aspects and communication culture; media systems and regulatory policy; as well as methods of media economics. The handbook is a must-read for students, teachers and researchers in media and communication economics and science,as well as practicioners and policy-makers at the nexus of media, business and politics.
Keywords: Department Medien und Digitale Technologien